(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To compare the rate of infection and fracture union in reamed versus unreamed interlocked IM nailing in patients with open tibia fractures. Methods: It was prospective comparative study done at Department of Orthopedics, Sheikh Zayed Hospital, Rahim Yar khan. 100 patients were enrolled who fulfilled the inclusion criteria and were divided randomly into two groups i.e. 50 in each group. Patients in Group A underwent unreamed IM nailing, whereas Group B underwent reamed IM nailing and patients were followed up at 2, 6, 12 weeks and then at 6 months for assessment of outcomes. Results: The mean age of the patients in Group A was 378.3 years and in the Group B, it was 368.49 years. In Group A versus B, fracture union occurred in 40 (40%) and 47 (47%) patients (p=0.037) and SSI occurred in 2 (4%) and 5 (10%) patients (p=0.240), respectively. Conclusion: Reamed IM interlocking nail was better in terms of fracture union compared to unreamed nail and there was no significant difference in terms of frequency of SSI between both interventions.